Rancang Bangun Perangkat Flow Meter Reading Analog Konevensional - Ramdhani, Fiqri; Aziz, Arif Abdul; Fakhrurroja, Hanif (eProceedings of Engineering, 2024)
PDAM is a regional company that provides water supply services to all residents of the Indonesian Community in need. PDAM checks the amount of water usage of each customer every month by sending officers to the customer's house to check and record the amount of water usage through the water meter. The water meters used by PDAM are still analog in nature so that customers experience difficulties in reading the amount of water usage [1]. Because water recording is still manual and analog tools. So to help development innovation, the first step is to create a PDAM water usage monitoring system in digital form. Flow Meter Reading is the development of a device that will be used to read analog water meters that measure fluid volumetric flow rates digitally. The use of manual water meters that are still manually recorded by employees will be helped by the presence of Analog Flow Meter Reading devices, Flow Meter Reading device design is carried out. The design is done by making a PCB design using a low power MCU STM32. Keywords-Water, PDAM Customer, Water Meter, Monitoring